Kunst in de bajes : rijksgebouwen. - Dekker, Ger; Kerkvliet, Gerard; Maters, Bas; Patijn, Wytze; Spijkerman, Sandra; van den Berg, Jaap (Rotterdam : Uitgeverij 010 Rotterdam, 1997)
Van de Beek, Felix ; Belzer, George ; Benus, Anna Thalia ; Besemer, Theo ; Besems, Korrie ; Bezemer, Nic ; Bisschops, Jac ; Blok, Diana ; Boezem, Marinus ; van den Boomen, Tom ; Bos, Loek ; van den Bosch, Rinus ; Brasser, Fons ; Broekman, Barbara ; Budding, Allard ; Buisman, Sjoerd ; Dallinga, Siert ; Dekkers, Ger ; van Delft, Ceciel ; Diepraam, Willem ; Dings, Nicolas ; Doorenweerd, Jeroen ; van Elk, Maria ; Galis, Vera ; Gravemaker, Moc ; De Groot, Arie ; van Hanegem, Ab ; Heemsbergen, Kor ; Heringa, Liet ; Janssen, Edwin ; de Jong, Tije ; Jongenelis, Hewald ; Kaap, Gerald Van Der ; van Kalsbeek, Maarten ; Kattenberg, Peter ; Kloosterboer, Klaas ; de Koning, Krijn ; Koorstra, Peter ; van der Kraan, Axel & Helena ; van der Linden, Thomas ; van Loon, Barbara ; de Looper, Henk ; Makkink, Herman ; Mater, Ilse ; Maters, Bas ; Moll, Gerrie ; Müller, Pjotr ; Nouwens, Herbert ; Olaf, Erwin ; Oudendijk, Sonja ; Pander, Arnold ; Pennock, Lon ; Ploeg, Maarten ; Polhuis, Gerard ; Post, Volkert ; Prent, Gerard ; Raaijman, Ben ; de Rooij, Jacobien ; Schorbach, Alice ; Schouwenberg, Louise ; Semier, Anne ; Somers, Michel ; Terpstra, Rein Jelle ; Visch, Henk ; Wevers, Kees ; de Weyer, Tine van ; Wielaert, Jasper J. ; de Wint, RW van ; de Wolf, Lam ; Zijlmans, Sylvie
boek
Keywords: Nederland